2012
DOI: 10.1111/jfpp.12028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Freeze-Drying Treatment on the Aromatic Profile of Tuber spp. Truffles

Abstract: The influence of lyophilization on the aromatic profile of two different truffles from Spain (Tuber melanosporum and Tuber aestivum) and a cultivated truffle (Tuber indicum) was evaluated by means of the headspace analysis. The volatile compounds were separated by gas chromatography and identified by mass spectrometry. The truffle aroma contained the characteristic compounds, such as 2‐methyl‐1‐propanol, 2‐methyl‐1‐butanol and dimethyl sulfide. Lyophilization and the subsequent rehydration of the truffles did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Al-Ruqaie demonstrated that freezing after blanching in 4% boiling NaCl solution is the most effective preservation method for maintaining the quality of T. claveryi and T. nivea [120]. Rivera et al recommended lyophilization as an adequate method to better preserve the aroma of T. melanosporum, while Palacios et al suggested that rehydration after lyophilization recovered the aromatic profile changed through lyophilization [121,122]. According to Tirillini et al [123], the addition of 10% linoleic acid (w/w) significantly reduced total bacterial load and enhance the nutritional value of truffle sauce.…”
Section: Various Factors Affecting Productivity and Quality Of Trufflesmentioning
confidence: 99%
“…Al-Ruqaie demonstrated that freezing after blanching in 4% boiling NaCl solution is the most effective preservation method for maintaining the quality of T. claveryi and T. nivea [120]. Rivera et al recommended lyophilization as an adequate method to better preserve the aroma of T. melanosporum, while Palacios et al suggested that rehydration after lyophilization recovered the aromatic profile changed through lyophilization [121,122]. According to Tirillini et al [123], the addition of 10% linoleic acid (w/w) significantly reduced total bacterial load and enhance the nutritional value of truffle sauce.…”
Section: Various Factors Affecting Productivity and Quality Of Trufflesmentioning
confidence: 99%
“…In previous studies, it has been reported that the lyophilization technique has significantly benefited in preserving phenolic compounds, color pigments (anthocyanins, carotenoids, etc. ), ascorbic acid, aroma components, and textural properties in fruits and vegetables (Bhatta et al., 2020; Gümüşay, Borazan, Ercal, & Demirkol, 2015; Palacios, Guillamón, García‐Lafuente, & Villares, 2014; Rajkumar et al., 2017; Rodrigues, Dos Santos, Bergamasco, & Madrona, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of storage and freezing on the volatile organic compounds (VOCs) profile, and subsequently on truffle aroma, has recently been reported (Culleré et al 2013;Pennazza et al 2013). Given that lyophilisation is performed at low temperatures, limiting the loss and degradation of volatile compounds, Palacios et al (2014) have recently tested it as a process for preserving truffles during storage. These authors showed that the aromatic profile of the species T. melanosporum and Tuber indicum was mainly maintained after lyophilisation, whereas the aromatic profile of Tuber aestivum was highly sensitive to this treatment and substantially modified.…”
Section: Monitoring the Impact Of Post-harvest Storage On The Qualitymentioning
confidence: 99%